Policy Uncertainty, Financialization and Enterprise Technological Innovation: A Way Forward Towards Economic Development - Zhang, Yan; Zhuo, Chengfeng; Deng, Feng (Frontiers in Environmental Science, 2022)
Technological innovation is the core factor for enterprises to maintain competitiveness. This paper aims to investigate how policy uncertainty affect enterprises’ innovation. On the basis of theoretical analysis, this study selects data from 2008-2017- and a share of non-financial listed companies as the research sample. Using patent data of listed companies and China's economic policy uncertainty (EPU) index, the study examines the impact of EPU on enterprise innovation. In addition, the regulatory effect of enterprise financialization has been investigated. The results show that the EPU can promote the quantity growth of enterprise innovation but inhibit the improvement of enterprise innovation quality. The impact of EPU on enterprise innovation will be affected by enterprise ownership, financing constraint level, life cycle, regional administrative level and regional economic level. Furthermore, enterprise financialization shows a negative regulatory effect in the process of EPU affecting enterprise innovation. This study provides policy enlightenment for reasonably formulating economic policies and promoting enterprise financialization, so as to effectively improve enterprise innovation ability and economic development.